2016
DOI: 10.4049/jimmunol.1402518
|View full text |Cite
|
Sign up to set email alerts
|

PcpA Promotes Higher Levels of Infection and Modulates Recruitment of Myeloid-Derived Suppressor Cells during Pneumococcal Pneumonia

Abstract: We used two different infection models to investigate the kinetics of the PcpA-dependent pneumococcal disease in mice. In a bacteremic pneumonia model, we observed a PcpA-dependent increase in bacterial burden in the lungs, blood, liver, BAL and spleens of mice at 24-hrs post infection. This PcpA-dependent effect on bacterial burden appeared earlier (within 12-hrs) in the focal-pneumonia model, which lacks bacteremia or sepsis. Histological changes show that the ability of pneumococci to make PcpA was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…PspA is the major choline binding protein found on the surface of the pneumococcus and is involved in resistance to complement [ 44 ]. Pneumococcal choline binding protein A, PcpA, not to be confused with the adhesin CbpA, has been demonstrated to play a vital role in modulating the host immune response by recruiting myeloid-derived suppressor cells and controlling the inflammatory environment within the lungs during pneumonia [ 45 ]. We are currently testing whether this occurs in the heart and is an additional explanation for the lack of immune cells associated with cardiac microlesions.…”
Section: Discussionmentioning
confidence: 99%
“…PspA is the major choline binding protein found on the surface of the pneumococcus and is involved in resistance to complement [ 44 ]. Pneumococcal choline binding protein A, PcpA, not to be confused with the adhesin CbpA, has been demonstrated to play a vital role in modulating the host immune response by recruiting myeloid-derived suppressor cells and controlling the inflammatory environment within the lungs during pneumonia [ 45 ]. We are currently testing whether this occurs in the heart and is an additional explanation for the lack of immune cells associated with cardiac microlesions.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the proteins were transferred to phenylmethylsulfonyl fluoride membrane and blocked with 3% bovine serum albumin (BSA) in PBS with 0.1% Tween 20 (sigma). Expressed PspA were detected by using mouse anti-PspA ( Walker et al, 2016 ) and anti-mouse IgG conjugated HRP used as secondary antibodies. Images were obtained by using a ChemiDoc (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the proteins were transferred to phenylmethylsulfonyl fluoride membrane and blocked with 3% bovine serum albumin (BSA) in PBS with 0.1% Tween 20 (Sigma). Target proteins were detected by using each antibody: mouse anti-PspA ( Walker et al, 2016 ), rabbit- anti-GAPDH (Abcam) and mouse anti-PcpA ( Novicket al, 2017 ). Anti-rabbit IgG or anti-mouse IgG conjugated to alkaline phosphatase or HRP were used as secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…They also determined that dying neutrophils served as a major source of TRAIL, and hypothesized that an inability to induce macrophage apoptosis during early pneumococcal infection may explain the severe pathology of neutropenic hosts during pulmonary bacterial infection (85). Other factors inhibiting macrophage apoptosis, such as host-derived MIF or bacterial PcpA, have also been shown to be detrimental to the host during pneumococcal infection (86,87). For instance, recent research has demonstrated that AM-specific expression of the anti-apoptotic protein MCL-1 in mice inhibited the cells' capacity to kill phagocytosed S. pneumoniae.…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%